Development of Mathematics E-Comic Media Based On Problem Based Learning To Improve The Problem Solving Ability And Learning Interest of Students of Muhammadiyah Private Junior High School 16 Lubuk Pakam - Irmaya, Nia; Syahputra, Hermawan; Lubis, Asrin (Mathline : Jurnal Matematika dan Pendidikan Matematika, 2024)
This research intends to (1) create valid, practical, and successful PBL-based E-Comics media; (2) evaluating Problem-Based Learning-based E-Comics media for problem-solving improvement; (3) examining student enthusiasm in learning with Problem-Based Learning e-comics medium. This study follows the ADDIE model—analysis, design, development, implementation, and evaluation. This study included SMP Muhammadiyah 16 Lubuk Pakam seventh-graders. RPP, LKPD, problem-solving ability exam, and student learning interest questionnaire are used to create e-comic media. The results showed that (1) Media E-Comics based Problem Based Learning (PBL) to improve problem-solving skills and interest in learning met valid criteria with a score of 4.69; (2) The practical criteria in the second practical test included observation of learning using E-Comics media with a score of 88.15%, teacher response of 87.94%, and student response of 90.75%; and (3) E-Comics media meets effectiveness criteria; (i) Problem-solving skills in the effectiveness test I rose by 0.68 with a medium category at pretest and posttest. Comparing posttest I and II values ​​showed that test II was more effective with N-gain 0.43 in the medium category; (ii) increased student interest in learning effectiveness test I with an average of 96.87%, with 8 excellent, 23 good, and 1 sufficient students. effectiveness test II followed with an average of 100%, with 17 excellent and 15 good students.